Desain dan Implementasi Media Video Prinsip-Prinsip Alat Ukur Listrik dan Elektronika - Fechera, Boy; Somantri, Maman; Hamik, Dadang Lukman (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This study describes the design process and implementation of video media in learning the electrical and electronic measuring instruments principles.The purpose of making this media to improve students understanding of the principles of electrical and electronic measuring instruments, include teaching materials about the gauge multimeters, the voltmeter and amperemeter. Research procedure followed the steps of research and development. Data collection was done by assigning kuersioner and structured interviews. The results showed that the learning conditions is still conventional, the use of video-based learning media has been tested and positive impact on student responses and help students and teachers in the learning process. The implication is expected to have an impact on teachers increased innovation in the use of instructional media.